104k views
5 votes
Find the dr/d(theta) for:
r = (theta)sin(theta) + cos(theta)​

Find the dr/d(theta) for: r = (theta)sin(theta) + cos(theta)​-example-1
User HokaHelal
by
5.5k points

1 Answer

6 votes


r=\theta\sin\theta+\cos\theta


(\mathrm dr)/(\mathrm d\theta)=(\mathrm d(\theta\sin\theta))/(\mathrm d\theta)+(\mathrm d(\cos\theta))/(\mathrm d\theta)

By the product rule,


(\mathrm d(\theta\sin\theta))/(\mathrm d\theta)=(\mathrm d(\theta))/(\mathrm d\theta)\sin\theta+\theta(\mathrm d(\sin\theta))/(\mathrm d\theta)=\sin\theta+\theta\cos\theta

and


(\mathrm d(\cos\theta))/(\mathrm d\theta)=-\sin\theta

So we have


(\mathrm dr)/(\mathrm d\theta)=\sin\theta+\theta\cos\theta-\sin\theta


\implies(\mathrm dr)/(\mathrm d\theta)=\theta\cos\theta

User Alaor
by
5.2k points